PELAKSANAAN PROMOSI PENJUALAN TIKET PESAWAT DI PT. PRIMA RIAU HOLIDAY PEKANBARU - Nisaq, Khoirun; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The purpose of this study was to investigate the implementation of ticket salespromotion in Prima Riau Holiday Pekanbaru and learn respondents to the implementation of ticket sales by Prima Vacation Riau Pekanbaru using promotional mix consists of advertising, personal selling and sales promotion .This study uses Tjiptono theory (2008) .And using quantitative research methods descriptive approach. According to Mohammad Nazir (2011: 86) design planning study aims to conduct research to get the logic in making conclusions. Good design research plan will be able to translate scientific models in practical operational research. Every step of the planning study design requires making the right decision by the researcher. techniques of data collection is done by means of observation and questionnaire interview. Researchers set the number of respondents to fill out the questionnaire as much as 84 people.Prima Riau Holiday Pekanbaru has been carrying out such promotion with advertising, sales promotion and sales of individual / personal selling. For advertising, Prima Riau Holiday Pekanbaru using multiple media such as advertising banners and boards. For sales promotion carried out by following the exhibition and the provision of rebates / discounts, while for individual sales by conducting field selling and retail selling. Respondents on the implementation of the campaign has been conducted by PT Prima Riau Holiday Pekanbaru is still not good. It can be seen from the respondents to the questionnaire that has been deployed by the researcher, namely for advertising respondents gave ratings hesitation, sales promotion rated doubtful and sale of individual / personal selling assessed agree.Keywords: Promotion, Ticket, Responden, Advertising.